The Characteristics of Necessity, Commoner, and Parasite with Multicultural Data Comparison - Kim, Chong; Song, Young; Kim, Nam (Journal of Comparative International Management, 2014)
Three different types of employees can be found in workplaces all over the world: “Necessities,” “Commoners,” and “Parasites.” A person is a Necessity if s/he is irreplaceable and crucial to the functioning of an organization. A Commoner is a person of normal ability and talent who has no significant impact on organizational success. Parasites are detrimental freeloaders who damage the functioning of an organization. To identify the principal characteristics of these three types of workers, a group of researchers led by Chong W. Kim conducted six studies in which they collected survey data from undergraduate and graduate business students in the U.S., India, Korea, Chile, and Japan. The results of this research effort are reported in Kim & Sikula (2005), Kim & Sikula (2006), Kim, Sikula & Smith (2006), Kim, Cho & Sikula (2007), Kim, Arias- Bolzmann & Smith (2008), and Kim, Arias-Bolzmann & Magoshi (2009). The summary of these six studies has been reported in Kim, Smith, Sikula & Anderson (2011). The purpose of this article is to compare the results of the summary study with a new set of data, which was collected from a multicultural student body. The authors note the points of commonality between the data sets and offer their thoughts on future research in this area.